Ultrahigh molecular weight polyethylene fiber and preparation method thereof
By introducing composite flame retardant, modified nano-titanium dioxide and modified α-zirconium phosphate into ultra-high molecular weight polyethylene fibers, and modifying the flame retardant of traditional fibers is solved by using tannin acid and silane coupling agents for modification. , the shortcomings in heat resistance and processability have achieved higher performance improvements.
Patent Information
- Application Number
- CN202411637904.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2024-12-17
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional ultra-high molecular weight polyethylene fibers are difficult to meet higher industrial standards in terms of flame retardancy, heat resistance, aging resistance and processability.
Combined with composite flame retardant, modified nanotitanium dioxide, modified α-zirconium phosphate and tanninic acid modified solution and silane coupling agent, the flame retardant, mechanical properties and thermal stability of the fiber are improved through modification treatment, and The fibers are enhanced by spinning and impregnation processes.
It significantly improves the flame retardant properties, mechanical properties and thermal stability of the fiber, enhances the processing performance, and meets higher industrial standards.
Smart Images

Figure 8RN55TEDTYECDP89FKTX7YSHVHEBOHBHUCT329RV
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer fibers, and in particular to an ultra-high molecular weight polyethylene fiber and a preparation method thereof. Background Art
[0002] Ultra-high molecular weight polyethylene fiber, with its excellent physical and mechanical properties, such as high strength, high modulus, wear resistance and chemical stability, has been widely used in many industrial fields. However, with the advancement of science and technology and the continuous expansion of application fields, the performance requirements for ultra-high molecular weight polyethylene fibers are also increasing. Traditional ultra-high molecular weight polyethylene fibers have gradually become difficult to meet higher standards in some specific properties, such as flame retardancy, heat resistance, aging resistance and processability.
[0003] At present, some methods have been tried to improve the above properties of ultra-high molecular weight polyethylene fibers by adding flame retardants, antioxidants or adopting special processing techniques. However, in actual use, the ideal optimal state has not yet been achieved. Therefore, how to optimize the performance of traditional ultra-high molecular weight polyethylene fibers by improving the preparation process has become a technical problem that needs to be urgently solved by technical personnel in this field. Summary of the invention
[0004] Technical issues solved In view of the above-mentioned shortcomings of the prior art, the present invention provides an ultra-high molecular weight polyethylene fiber and a preparation method thereof, which can effectively solve the problem that the flame retardancy, heat resistance, aging resistance and processability of the ultra-high molecular weight polyethylene fiber of the prior art still need to be improved.
[0005] Technical Solution To achieve the above objectives, the present invention is implemented through the following technical solutions: An ultra-high molecular weight polyethylene fiber, the ultra-high molecular weight polyethylene fiber is composed of the following components: ultra-high molecular weight polyethylene, a composite flame retardant, modified nano titanium dioxide, modified α-zirconium phosphate, tannic acid modification liquid and a silane coupling agent dispersion; The composite flame retardant is prepared by grafting 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide onto magnesium hydroxide; The modified nano titanium dioxide is prepared by modifying nano titanium dioxide with a silane coupling agent KH-570; The modified α-zirconium phosphate is prepared by modifying α-zirconium phosphate with trishydroxymethylaminomethane and vinyltriethoxysilane.
[0006] Furthermore, the preparation method of the composite flame retardant is: 10-12g 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and 1-2g silane coupling agent KH-560 are stirred at a temperature of 160°C and a stirring speed of 200r / min for 2h, 300mL anhydrous ethanol and 18-20g magnesium hydroxide are added, and then stirred at a temperature of 120°C and a stirring speed of 200r / min for 2h, the filtrate is filtered to remove the filtrate, and then placed in an oven at 120°C to dry for 2h, and the resultant is a composite flame retardant.
[0007] Furthermore, the preparation steps of the modified nano titanium dioxide are: Step 1, weigh 2g of nano titanium dioxide and disperse it in 200g of anhydrous ethanol, and after ultrasonic dispersion, heat and stir at 70°C for 2h, and after ultrasonic dispersion again, the result is recorded as titanium dioxide dispersion; Step 2: Disperse 5 g of silane coupling agent KH-570 in 100 g of anhydrous ethanol, stir at a stirring speed of 500 r / min for 10 min, and the result is recorded as a silane coupling agent dispersion; Step 3: add 2.5 mL of silane coupling agent dispersion to 100 mL of titanium dioxide dispersion, heat and stir at 70°C for 6 h, wash the precipitate with anhydrous ethanol 3 times after centrifugation, and then dry it in an oven at 80°C for 12 h to obtain modified nano titanium dioxide.
[0008] Furthermore, the specific operation of ultrasonic dispersion in step 1 is ultrasonic dispersion at a frequency of 27 kHz for 10 min, the stirring speed of heated stirring in step 1 is 300 r / min, the dripping rate in step 3 is 1 drop / s, the stirring speed of heated stirring in step 3 is 400 r / min, and the specific operation of centrifugal treatment in step 3 is centrifugation at a centrifugal speed of 10000 r / min for 5 min.
[0009] Furthermore, the preparation steps of the modified α-zirconium phosphate are: Step = 1 \* ROMAN \* MERGEFORMAT I. Weigh 5 g of α-zirconium phosphate and mix with 300 mL of deionized water. The result after uniform dispersion is recorded as α-zirconium phosphate dispersion. Weigh 3 g of tris(hydroxymethyl)aminomethane and dissolve it in 50 mL of deionized water. The result after uniform mixing is recorded as tris(hydroxymethyl)aminomethane solution. Step = 2 \* ROMAN \* MERGEFORMAT II, drip the tris(hydroxymethyl)aminomethane) solution into the α-zirconium phosphate dispersion at a dripping rate of 3 mL / min, perform ultrasonic treatment at a frequency of 40 kHz for 20 min after dripping, let stand for 24 h, perform centrifugal treatment to obtain a precipitate, wash the precipitate with deionized water for 3 times, freeze-dry for 48 h, and record it as exfoliated α-zirconium phosphate; Step = 3 \* ROMAN \* MERGEFORMAT III, disperse 3.5g of exfoliated α-zirconium phosphate, 350mL of anhydrous ethanol, 20mL of deionized water and 3.5mL of vinyltriethoxysilane in a flask, distill at 80°C and reflux with cooling water on the top for 4h, wash the distillate twice with anhydrous ethanol and once with deionized water, and freeze-dry for 48h to obtain the modified α-zirconium phosphate.
[0010] Furthermore, the specific operation for uniform dispersion in step = 1 \* ROMAN \* MERGEFORMAT I is stirring at a stirring speed of 500 r / min for 10 min, the specific operation for uniform mixing in step = 1 \* ROMAN \* MERGEFORMAT I is stirring at a stirring speed of 300 r / min for 10 min, and the specific operation for centrifugal treatment in step = 2 \* ROMAN \* MERGEFORMAT II is centrifugal treatment at a centrifugal speed of 6000 r / min for 5 min.
[0011] Furthermore, the preparation method of the tannic acid modified liquid is: 0.4 g of tris(hydroxymethyl)aminomethane), 2.5 g of sodium chloride, 0.6 g of tannic acid and 150 mL of deionized water were mixed, stirred at a stirring speed of 300 r / min for 10 min, and then a 1 mol / L hydrochloric acid solution was added dropwise to adjust the pH value to 8.5. The result was a tannic acid modified solution.
[0012] Furthermore, the preparation method of the silane coupling agent dispersion is: 6 g of silane coupling agent KH-550 was weighed and dispersed in 100 mL of deionized water, and ultrasonically dispersed at a frequency of 28 kHz for 30 minutes to obtain a silane coupling agent dispersion.
[0013] A method for preparing ultra-high molecular weight polyethylene fiber, the preparation method comprising: S1, pouring 100 parts by weight of ultra-high molecular weight polyethylene, 20-25 parts by weight of composite flame retardant, 2-3 parts by weight of modified nano titanium dioxide and 3-4 parts by weight of modified α-zirconium phosphate into an internal mixer, mixing and spinning into fibers through a spinning machine, and the obtained fibers are recorded as the fibers to be treated; S2, immersing the fiber to be treated in tannic acid modification liquid at a solid-liquid ratio of 1:20, shaking at room temperature for 38 hours, removing the filtrate and rinsing with deionized water for 3 times, and recording the initial modified fiber component after drying; S3. Immerse the primary modified fiber component in a silane coupling agent dispersion according to a solid-liquid ratio of 1:20, remove the filtrate after stirring for reaction, and rinse with deionized water for 3 times. After drying, the obtained fiber is an ultra-high molecular weight polyethylene fiber.
[0014] Furthermore, the mixing temperature in S1 is 205°C, the mixing speed is 60r / min, the mixing time is 10min, the specific operation of the drying treatment in S2 is to place it in an oven at 60°C for 8h, and the specific operation of the drying treatment in S3 is to place it in an oven at 60°C for 12h.
[0015] Beneficial Effects The present invention provides an ultra-high molecular weight polyethylene fiber and a preparation method thereof. Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention introduces a composite flame retardant, modified nano titanium dioxide and modified α-zirconium phosphate into ultra-high molecular weight polyethylene, which can improve flame retardancy, mechanical properties and thermal stability; 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and magnesium hydroxide are compounded, which can combine the flame retardancy mechanism of phosphorus and inorganic hydroxides, form a protective layer during the combustion process and effectively prevent the spread of flames, thereby significantly improving the flame retardancy of the fiber; secondly, after the nano titanium dioxide and α-zirconium phosphate are modified, the surface properties are improved, the compatibility with the polyethylene matrix is enhanced, and they can be uniformly dispersed in the matrix. They are introduced into ultra-high molecular weight polyethylene through melt blending and can serve as physical crosslinking points, thereby increasing the interaction force between polyethylene molecular chains and improving the mechanical properties and thermal stability of the fiber.
[0016] 2. The present invention sequentially immerses the fiber to be treated in a tannic acid modification liquid and a silane coupling agent dispersion for modification, which enables the tannic acid to react with functional groups such as hydroxyl groups on the fiber surface to form chemical bonds, thereby increasing the polarity and hydrophilicity of the fiber surface and facilitating subsequent treatment. The silane coupling agent can react with the fiber surface and the inorganic particle surface at the same time to form a "bridging" structure, further enhancing the interaction between the fiber and the inorganic particles and improving the processing performance and mechanical properties of the fiber. DETAILED DESCRIPTION
[0017] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0018] The present invention will be further described below in conjunction with the embodiments.
[0019] An ultra-high molecular weight polyethylene fiber of this embodiment, the ultra-high molecular weight polyethylene fiber is composed of the following components: ultra-high molecular weight polyethylene, composite flame retardant, modified nano titanium dioxide, modified α-zirconium phosphate, tannic acid modification liquid and silane coupling agent dispersion; The composite flame retardant is prepared by grafting 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide onto magnesium hydroxide; Modified nano titanium dioxide is prepared by modifying nano titanium dioxide with silane coupling agent KH-570; The modified alpha-zirconium phosphate is prepared by modifying alpha-zirconium phosphate with trishydroxymethylaminomethane and vinyltriethoxysilane.
[0020] The preparation method of the composite flame retardant is: 10 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and 1 g of silane coupling agent KH-560 were stirred at a temperature of 160° C. and a stirring speed of 200 r / min for 2 h, 300 mL of anhydrous ethanol and 18 g of magnesium hydroxide were added, and the mixture was stirred at a temperature of 120° C. and a stirring speed of 200 r / min for 2 h. The filtrate was filtered to remove the filtrate, and then dried in an oven at 120° C. for 2 h to obtain a composite flame retardant.
[0021] The preparation steps of modified nano titanium dioxide are: Step 1, weigh 2g of nano titanium dioxide and disperse it in 200g of anhydrous ethanol, disperse it ultrasonically at a frequency of 27kHz for 10min, then heat and stir it at a temperature of 70°C and a stirring speed of 300r / min for 2h, and disperse it ultrasonically again to obtain a titanium dioxide dispersion; Step 2, dispersing 5 g of silane coupling agent KH-570 in 100 g of anhydrous ethanol, stirring at a stirring speed of 500 r / min for 10 min, and the resultant is recorded as a silane coupling agent dispersion; Step 3: Add 2.5 mL of silane coupling agent dispersion to 100 mL of titanium dioxide dispersion at a dropping rate of 1 drop / s. Heat and stir at 70°C and 400 r / min for 6 h. Centrifuge at 10,000 r / min for 5 min, wash the precipitate three times with anhydrous ethanol, and then dry it in an oven at 80°C for 12 h to obtain modified nano titanium dioxide.
[0022] The preparation steps of modified α-zirconium phosphate are: Step = 1 \* ROMAN \* MERGEFORMAT I. Weigh 5 g of α-zirconium phosphate and mix with 300 mL of deionized water, stir at a stirring speed of 500 r / min for 10 min, and the result is recorded as α-zirconium phosphate dispersion; weigh 3 g of tris(hydroxymethylaminomethane) and dissolve it in 50 mL of deionized water, stir at a stirring speed of 300 r / min for 10 min, and the result is recorded as tris(hydroxymethylaminomethane) solution; Step = 2 \* ROMAN \* MERGEFORMAT II, drip the tris(hydroxymethyl)aminomethane) solution into the α-zirconium phosphate dispersion at a dripping rate of 3 mL / min, perform ultrasonic treatment at a frequency of 40 kHz for 20 min after dripping, let stand for 24 h, centrifuge at a centrifugal speed of 6000 r / min for 5 min to obtain a precipitate, wash the precipitate with deionized water for 3 times, freeze-dry for 48 h, and record it as exfoliated α-zirconium phosphate; Step = 3 \* ROMAN \* MERGEFORMAT III, disperse 3.5g of exfoliated α-zirconium phosphate, 350mL of anhydrous ethanol, 20mL of deionized water and 3.5mL of vinyltriethoxysilane in a flask, distill at 80°C and reflux with cooling water on the top for 4h, wash the distillate twice with anhydrous ethanol and once with deionized water, and freeze-dry for 48h to obtain the modified α-zirconium phosphate.
[0023] The preparation method of tannic acid modified liquid is as follows: 0.4 g of tris(hydroxymethyl)aminomethane), 2.5 g of sodium chloride, 0.6 g of tannic acid and 150 mL of deionized water were mixed, stirred at a stirring speed of 300 r / min for 10 min, and then a 1 mol / L hydrochloric acid solution was added dropwise to adjust the pH value to 8.5. The result was a tannic acid modified solution.
[0024] The preparation method of the silane coupling agent dispersion is as follows: 6 g of silane coupling agent KH-550 was weighed and dispersed in 100 mL of deionized water, and ultrasonically dispersed at a frequency of 28 kHz for 30 minutes to obtain a silane coupling agent dispersion.
[0025] A method for preparing ultra-high molecular weight polyethylene fiber, the preparation method comprising: S1, pouring 100 parts by weight of ultra-high molecular weight polyethylene, 20 parts by weight of composite flame retardant, 2 parts by weight of modified nano titanium dioxide and 3 parts by weight of modified α-zirconium phosphate into an internal mixer, mixing and spinning into fibers through a spinning machine, the obtained fibers are recorded as the treated fibers, the internal mixing temperature is 205° C., the internal mixing speed is 60 r / min, and the internal mixing time is 10 min; S2, immersing the fiber to be treated in tannic acid modification liquid at a solid-liquid ratio of 1:20, shaking at room temperature for 38 hours, removing the filtrate and rinsing with deionized water for 3 times, placing in an oven at 60°C and drying for 8 hours, and recording as the initial modified fiber component; S3. Immerse the primary modified fiber component in a silane coupling agent dispersion at a solid-liquid ratio of 1:20, remove the filtrate after stirring for reaction, rinse with deionized water for 3 times, and dry in an oven at 60°C for 12 hours to obtain an ultra-high molecular weight polyethylene fiber.
[0026] An ultra-high molecular weight polyethylene fiber of this embodiment, the ultra-high molecular weight polyethylene fiber is composed of the following components: ultra-high molecular weight polyethylene, composite flame retardant, modified nano titanium dioxide, modified α-zirconium phosphate, tannic acid modification liquid and silane coupling agent dispersion; The composite flame retardant is prepared by grafting 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide onto magnesium hydroxide; Modified nano titanium dioxide is prepared by modifying nano titanium dioxide with silane coupling agent KH-570; The modified alpha-zirconium phosphate is prepared by modifying alpha-zirconium phosphate with trishydroxymethylaminomethane and vinyltriethoxysilane.
[0027] The preparation method of the composite flame retardant is: 12 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and 2 g of silane coupling agent KH-560 were stirred at 160° C. and 200 r / min for 2 h, 300 mL of anhydrous ethanol and 20 g of magnesium hydroxide were added, and the mixture was stirred at 120° C. and 200 r / min for 2 h. The filtrate was filtered to remove the filtrate, and then dried in an oven at 120° C. for 2 h to obtain a composite flame retardant.
[0028] The preparation steps of modified nano titanium dioxide are: Step 1, weigh 2g of nano titanium dioxide and disperse it in 200g of anhydrous ethanol, disperse it ultrasonically at a frequency of 27kHz for 10min, then heat and stir it at a temperature of 70°C and a stirring speed of 300r / min for 2h, and disperse it ultrasonically again to obtain a titanium dioxide dispersion; Step 2, dispersing 5 g of silane coupling agent KH-570 in 100 g of anhydrous ethanol, stirring at a stirring speed of 500 r / min for 10 min, and the resultant is recorded as a silane coupling agent dispersion; Step 3: Add 2.5 mL of silane coupling agent dispersion to 100 mL of titanium dioxide dispersion at a dropping rate of 1 drop / s. Heat and stir at 70°C and 400 r / min for 6 h. Centrifuge at 10,000 r / min for 5 min, wash the precipitate three times with anhydrous ethanol, and then dry it in an oven at 80°C for 12 h to obtain modified nano titanium dioxide.
[0029] The preparation steps of modified α-zirconium phosphate are: Step = 1 \* ROMAN \* MERGEFORMAT I. Weigh 5 g of α-zirconium phosphate and mix with 300 mL of deionized water, stir at a stirring speed of 500 r / min for 10 min, and the result is recorded as α-zirconium phosphate dispersion; weigh 3 g of tris(hydroxymethylaminomethane) and dissolve it in 50 mL of deionized water, stir at a stirring speed of 300 r / min for 10 min, and the result is recorded as tris(hydroxymethylaminomethane) solution; Step = 2 \* ROMAN \* MERGEFORMAT II, drip the tris(hydroxymethyl)aminomethane) solution into the α-zirconium phosphate dispersion at a dripping rate of 3 mL / min, perform ultrasonic treatment at a frequency of 40 kHz for 20 min after dripping, let stand for 24 h, centrifuge at a centrifugal speed of 6000 r / min for 5 min to obtain a precipitate, wash the precipitate with deionized water for 3 times, freeze-dry for 48 h, and record it as exfoliated α-zirconium phosphate; Step = 3 \* ROMAN \* MERGEFORMAT III, disperse 3.5g of exfoliated α-zirconium phosphate, 350mL of anhydrous ethanol, 20mL of deionized water and 3.5mL of vinyltriethoxysilane in a flask, distill at 80°C and reflux with cooling water on the top for 4h, wash the distillate twice with anhydrous ethanol and once with deionized water, and freeze-dry for 48h to obtain the modified α-zirconium phosphate.
[0030] The preparation method of tannic acid modified liquid is as follows: 0.4 g of tris(hydroxymethyl)aminomethane), 2.5 g of sodium chloride, 0.6 g of tannic acid and 150 mL of deionized water were mixed, stirred at a stirring speed of 300 r / min for 10 min, and then a 1 mol / L hydrochloric acid solution was added dropwise to adjust the pH value to 8.5. The result was a tannic acid modified solution.
[0031] The preparation method of the silane coupling agent dispersion is as follows: 6 g of silane coupling agent KH-550 was weighed and dispersed in 100 mL of deionized water, and ultrasonically dispersed at a frequency of 28 kHz for 30 minutes to obtain a silane coupling agent dispersion.
[0032] A method for preparing ultra-high molecular weight polyethylene fiber, the preparation method comprising: S1, pouring 100 parts by weight of ultra-high molecular weight polyethylene, 25 parts by weight of composite flame retardant, 3 parts by weight of modified nano titanium dioxide and 4 parts by weight of modified α-zirconium phosphate into an internal mixer, mixing and spinning into fibers through a spinning machine, the obtained fibers are recorded as the treated fibers, the internal mixing temperature is 205° C., the internal mixing speed is 60 r / min, and the internal mixing time is 10 min; S2, immersing the fiber to be treated in tannic acid modification liquid at a solid-liquid ratio of 1:20, shaking at room temperature for 38 hours, removing the filtrate and rinsing with deionized water for 3 times, placing in an oven at 60°C and drying for 8 hours, and recording as the initial modified fiber component; S3. Immerse the primary modified fiber component in a silane coupling agent dispersion at a solid-liquid ratio of 1:20, remove the filtrate after stirring for reaction, rinse with deionized water for 3 times, and dry in an oven at 60°C for 12 hours to obtain an ultra-high molecular weight polyethylene fiber.
[0033] An ultra-high molecular weight polyethylene fiber of this embodiment, the ultra-high molecular weight polyethylene fiber is composed of the following components: ultra-high molecular weight polyethylene, composite flame retardant, modified nano titanium dioxide, modified α-zirconium phosphate, tannic acid modification liquid and silane coupling agent dispersion; The composite flame retardant is prepared by grafting 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide onto magnesium hydroxide; Modified nano titanium dioxide is prepared by modifying nano titanium dioxide with silane coupling agent KH-570; The modified alpha-zirconium phosphate is prepared by modifying alpha-zirconium phosphate with trishydroxymethylaminomethane and vinyltriethoxysilane.
[0034] The preparation method of the composite flame retardant is: 11 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and 2 g of silane coupling agent KH-560 were stirred at 160° C. and 200 r / min for 2 h, 300 mL of anhydrous ethanol and 19 g of magnesium hydroxide were added, and the mixture was stirred at 120° C. and 200 r / min for 2 h. The filtrate was filtered to remove the filtrate, and then dried in an oven at 120° C. for 2 h to obtain a composite flame retardant.
[0035] The preparation steps of modified nano titanium dioxide are: Step 1, weigh 2g of nano titanium dioxide and disperse it in 200g of anhydrous ethanol, disperse it ultrasonically at a frequency of 27kHz for 10min, then heat and stir it at a temperature of 70°C and a stirring speed of 300r / min for 2h, and disperse it ultrasonically again to obtain a titanium dioxide dispersion; Step 2: Disperse 5 g of silane coupling agent KH-570 in 100 g of anhydrous ethanol, stir at a stirring speed of 500 r / min for 10 min, and the result is recorded as a silane coupling agent dispersion; Step 3: Add 2.5 mL of silane coupling agent dispersion to 100 mL of titanium dioxide dispersion at a dropping rate of 1 drop / s. Heat and stir at 70°C and 400 r / min for 6 h. Centrifuge at 10,000 r / min for 5 min, wash the precipitate three times with anhydrous ethanol, and then dry it in an oven at 80°C for 12 h to obtain modified nano titanium dioxide.
[0036] The preparation steps of modified α-zirconium phosphate are: Step = 1 \* ROMAN \* MERGEFORMAT I. Weigh 5 g of α-zirconium phosphate and mix with 300 mL of deionized water, stir at a stirring speed of 500 r / min for 10 min, and the result is recorded as α-zirconium phosphate dispersion; weigh 3 g of tris(hydroxymethylaminomethane) and dissolve it in 50 mL of deionized water, stir at a stirring speed of 300 r / min for 10 min, and the result is recorded as tris(hydroxymethylaminomethane) solution; Step = 2 \* ROMAN \* MERGEFORMAT II, drip the tris(hydroxymethyl)aminomethane) solution into the α-zirconium phosphate dispersion at a dripping rate of 3 mL / min, perform ultrasonic treatment at a frequency of 40 kHz for 20 min after dripping, let stand for 24 h, centrifuge at a centrifugal speed of 6000 r / min for 5 min to obtain a precipitate, wash the precipitate with deionized water for 3 times, freeze-dry for 48 h, and record it as exfoliated α-zirconium phosphate; Step = 3 \* ROMAN \* MERGEFORMAT III, disperse 3.5g of exfoliated α-zirconium phosphate, 350mL of anhydrous ethanol, 20mL of deionized water and 3.5mL of vinyltriethoxysilane in a flask, distill at 80°C and reflux with cooling water on the top for 4h, wash the distillate twice with anhydrous ethanol and once with deionized water, and freeze-dry for 48h to obtain the modified α-zirconium phosphate.
[0037] The preparation method of tannic acid modified liquid is as follows: 0.4 g of tris(hydroxymethyl)aminomethane), 2.5 g of sodium chloride, 0.6 g of tannic acid and 150 mL of deionized water were mixed, stirred at a stirring speed of 300 r / min for 10 min, and then a 1 mol / L hydrochloric acid solution was added dropwise to adjust the pH value to 8.5. The result was a tannic acid modified solution.
[0038] The preparation method of the silane coupling agent dispersion is as follows: 6 g of silane coupling agent KH-550 was weighed and dispersed in 100 mL of deionized water, and ultrasonically dispersed at a frequency of 28 kHz for 30 minutes to obtain a silane coupling agent dispersion.
[0039] A method for preparing ultra-high molecular weight polyethylene fiber, the preparation method comprising: S1, pouring 100 parts by weight of ultra-high molecular weight polyethylene, 23 parts by weight of composite flame retardant, 3 parts by weight of modified nano titanium dioxide and 3 parts by weight of modified α-zirconium phosphate into an internal mixer, mixing and spinning into fibers through a spinning machine, the obtained fibers are recorded as the fibers to be treated, the internal mixing temperature is 205° C., the internal mixing speed is 60 r / min, and the internal mixing time is 10 min; S2, immersing the fiber to be treated in tannic acid modification liquid at a solid-liquid ratio of 1:20, shaking at room temperature for 38 hours, removing the filtrate and rinsing with deionized water for 3 times, placing in an oven at 60°C and drying for 8 hours, and recording as the initial modified fiber component; S3. Immerse the primary modified fiber component in a silane coupling agent dispersion at a solid-liquid ratio of 1:20, remove the filtrate after stirring for reaction, rinse with deionized water for 3 times, and dry in an oven at 60°C for 12 hours to obtain an ultra-high molecular weight polyethylene fiber.
[0040] Comparative Example 1 The ultra-high molecular weight polyethylene fiber and the preparation method thereof provided in this comparative example are substantially the same as those in Example 1, with the main difference being that in this comparative example 1, the composite flame retardant in Example 1 is replaced with 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide.
[0041] Comparative Example 2 The ultra-high molecular weight polyethylene fiber and the preparation method thereof provided in this comparative example are substantially the same as those in Example 1, with the main difference being that in this comparative example 2, the modified nano titanium dioxide in Example 1 is replaced with unmodified nano titanium dioxide.
[0042] Comparative Example 3 The ultra-high molecular weight polyethylene fiber and the preparation method thereof provided in this comparative example are substantially the same as those in Example 1, with the main difference being that in this comparative example 3, the modified α-zirconium phosphate in Example 1 is replaced with unmodified α-zirconium phosphate.
[0043] Performance Testing The ultra-high molecular weight polyethylene fibers prepared in Examples 1-3 and Comparative Examples 1-3 are marked as Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2, and Comparative Example 3, respectively. Then, the properties of Examples 1-3 and Comparative Examples 1-3 are tested. The specific testing methods and test items are as follows: 1. The tensile strength and elongation at break of Examples 1-3 and Comparative Examples 1-3 were tested with reference to the standard of GB / T 1040.1-2018, and the obtained data are recorded in the following table; 2. The friction and wear properties of Examples 1-3 and Comparative Examples 1-3 were tested with reference to the standard of GB / T 3960-2016, and the obtained data are recorded in the following table; 3. The limiting oxygen index of Examples 1-3 and Comparative Examples 1-3 was tested with reference to the standard of GB / T 2406.2-2009, and the obtained data were recorded in the following table; It can be seen from the data in the above table that the ultra-high molecular weight polyethylene fibers in Examples 1-3 have better flame retardant properties than those in Comparative Example 1, indicating that the flame retardant effect of compounding 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and magnesium hydroxide is better than that of single 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide. Secondly, the ultra-high molecular weight polyethylene fibers in Examples 1-3 have better mechanical properties and friction properties than those in Comparative Examples 2-3, indicating that modifying nano-titanium dioxide and α-zirconium phosphate and then adding them to ultra-high molecular weight polyethylene can better improve the mechanical properties and wear resistance.
[0044] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0045] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. An ultra-high molecular weight polyethylene fiber, characterized in that: The ultra-high molecular weight polyethylene fiber is composed of the following components: ultra-high molecular weight polyethylene, composite flame retardant, modified nano titanium dioxide, modified α-zirconium phosphate, tannic acid modification liquid and silane coupling agent dispersion; The composite flame retardant is prepared by grafting 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide onto magnesium hydroxide; The modified nano titanium dioxide is prepared by modifying nano titanium dioxide with a silane coupling agent KH-570; The modified α-zirconium phosphate is prepared by modifying α-zirconium phosphate with trishydroxymethylaminomethane and vinyltriethoxysilane.
2. The ultra-high molecular weight polyethylene fiber according to claim 1, characterized in that: The preparation method of the composite flame retardant is: 10-12g 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and 1-2g silane coupling agent KH-560 are stirred at a temperature of 160°C and a stirring speed of 200r / min for 2h, 300mL anhydrous ethanol and 18-20g magnesium hydroxide are added, and then stirred at a temperature of 120°C and a stirring speed of 200r / min for 2h, the filtrate is filtered to remove the filtrate, and then placed in an oven at 120°C to dry for 2h, and the resultant is a composite flame retardant.
3. The ultra-high molecular weight polyethylene fiber according to claim 1, characterized in that: The preparation steps of the modified nano titanium dioxide are: Step 1, weigh 2g of nano titanium dioxide and disperse it in 200g of anhydrous ethanol, and then heat and stir at 70°C for 2h after ultrasonic dispersion, and then ultrasonically disperse it again to obtain a titanium dioxide dispersion; Step 2, dispersing 5 g of silane coupling agent KH-570 in 100 g of anhydrous ethanol, stirring at a stirring speed of 500 r / min for 10 min, and the resultant is recorded as a silane coupling agent dispersion; Step 3: add 2.5 mL of silane coupling agent dispersion to 100 mL of titanium dioxide dispersion, heat and stir at 70°C for 6 h, wash the precipitate with anhydrous ethanol 3 times after centrifugation, and then dry it in an oven at 80°C for 12 h to obtain modified nano titanium dioxide.
4. The ultra-high molecular weight polyethylene fiber according to claim 3, characterized in that: The specific operation of ultrasonic dispersion in step 1 is ultrasonic dispersion at a frequency of 27 kHz for 10 min, the stirring speed of heated stirring in step 1 is 300 r / min, the dripping rate in step 3 is 1 drop / s, the stirring speed of heated stirring in step 3 is 400 r / min, and the specific operation of centrifugal treatment in step 3 is centrifugal treatment at a centrifugal speed of 10000 r / min for 5 min.
5. The ultra-high molecular weight polyethylene fiber according to claim 1, characterized in that: The preparation steps of the modified α-zirconium phosphate are: Step = 1 \* ROMAN \* MERGEFORMAT I. Weigh 5 g of α-zirconium phosphate and mix with 300 mL of deionized water. The result after uniform dispersion is recorded as α-zirconium phosphate dispersion. Weigh 3 g of tris(hydroxymethyl)aminomethane and dissolve it in 50 mL of deionized water. The result after uniform mixing is recorded as tris(hydroxymethyl)aminomethane solution. Step = 2 \* ROMAN \* MERGEFORMAT II, drip the tris(hydroxymethyl)aminomethane) solution into the α-zirconium phosphate dispersion at a dripping rate of 3 mL / min, perform ultrasonic treatment at a frequency of 40 kHz for 20 min after dripping, let stand for 24 h, perform centrifugal treatment to obtain a precipitate, wash the precipitate with deionized water for 3 times, freeze-dry for 48 h, and record it as exfoliated α-zirconium phosphate; Step = 3 \* ROMAN \* MERGEFORMAT III, disperse 3.5g of exfoliated α-zirconium phosphate, 350mL of anhydrous ethanol, 20mL of deionized water and 3.5mL of vinyltriethoxysilane in a flask, distill at 80°C and reflux with cooling water on the top for 4h, wash the distillate twice with anhydrous ethanol and once with deionized water, and freeze-dry for 48h to obtain the modified α-zirconium phosphate.
6. The ultra-high molecular weight polyethylene fiber according to claim 5, characterized in that: The specific operation for uniform dispersion in step = 1 \*ROMAN \* MERGEFORMAT I is stirring at a stirring speed of 500 r / min for 10 min, the specific operation for uniform mixing in step = 1 \* ROMAN \* MERGEFORMAT I is stirring at a stirring speed of 300 r / min for 10 min, and the specific operation for centrifugal treatment in step = 2 \* ROMAN \* MERGEFORMAT II is centrifugal treatment at a centrifugal speed of 6000 r / min for 5 min.
7. The ultra-high molecular weight polyethylene fiber according to claim 1, characterized in that: The preparation method of the tannic acid modified liquid is: 0.4 g of tris(hydroxymethyl)aminomethane), 2.5 g of sodium chloride, 0.6 g of tannic acid and 150 mL of deionized water were mixed, stirred at a stirring speed of 300 r / min for 10 min, and then a 1 mol / L hydrochloric acid solution was added dropwise to adjust the pH value to 8.
5. The result was a tannic acid modified solution.
8. The ultra-high molecular weight polyethylene fiber according to claim 1, characterized in that: The preparation method of the silane coupling agent dispersion is: 6 g of silane coupling agent KH-550 was weighed and dispersed in 100 mL of deionized water, and ultrasonically dispersed at a frequency of 28 kHz for 30 minutes to obtain a silane coupling agent dispersion.
9. The method for preparing ultra-high molecular weight polyethylene fiber according to any one of claims 1 to 8, characterized in that: The preparation method is: S1, pouring 100 parts by weight of ultra-high molecular weight polyethylene, 20-25 parts by weight of composite flame retardant, 2-3 parts by weight of modified nano titanium dioxide and 3-4 parts by weight of modified α-zirconium phosphate into an internal mixer, mixing and spinning into fibers through a spinning machine, and the obtained fibers are recorded as the fibers to be treated; S2, immersing the fiber to be treated in tannic acid modification liquid at a solid-liquid ratio of 1:20, shaking at room temperature for 38 hours, removing the filtrate and rinsing with deionized water for 3 times, and recording the initial modified fiber component after drying; S3. Immerse the primary modified fiber component in a silane coupling agent dispersion according to a solid-liquid ratio of 1:20, remove the filtrate after stirring for reaction, and rinse with deionized water for 3 times. After drying, the obtained fiber is an ultra-high molecular weight polyethylene fiber.
10. The method for preparing ultra-high molecular weight polyethylene fiber according to claim 9, characterized in that: The temperature of the internal kneading and mixing in S1 is 205°C, the rotation speed of the internal kneading and mixing is 60r / min, the time of the internal kneading and mixing is 10min, the specific operation of the drying treatment in S2 is to place it in an oven at 60°C for 8h, and the specific operation of the drying treatment in S3 is to place it in an oven at 60°C for 12h.
Citation Information
Patent Citations
Preparation method for tannic acid modified ultrahigh molecular weight polyethylene fibers and composite material thereof
CN108395675A
Modified ultra-high molecular weight polyethylene fiber forming special material, and preparation method and melt spinning fiber forming method thereof
CN108660535A
Modified polyethylene composition with ultra-high molecular weight and preparation method thereof
CN111363227A
Flame-retardant ultra-high molecular weight polyethylene fiber and preparation method thereof
CN112359436A
Flame-retardant high-performance ultra-high molecular weight polyethylene composite fiber and preparation method thereof
CN112376125A
